TARTIB NUZULI DAN SIGNIFIKASINYA DALAM PENANGGALAN HIJRIYAH : Telaah Sejarah Turunnya Al-Qur'an (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
The process of the Qur'an descending has a special history, namely it was revealed gradually. This is one of the proofs of the truth of the revelation. The role of the recipient of revelation is very important as the key to the success of the Qur'an's goals. This study uses a library reasearch technique with a qualitative-descriptive method. Primary data collection from books, journal articles from previous research and secondary sources obtained by authors from other relevant literature sources. With the available data, the author analyzes to obtain the significance of Tartib Nuzuli to the determination of the beginning of the hijri year by using a historical chronological approach to the descent of the Qur'an. The first result, the concept of Nuzul's tartib is one of the proofs of the gradual descent of the Qur'an. Second, the first determination of the hijriyyah calendar in Islam cannot be separated from the history of the descent of the Qur'an which can be traced from Tartib Nuzuli, namely during the migration of the Prophet Muhammad PBUH to the city of Medina. This event became the initial milestone in the determination of the hijri calendar starting from the 1st of Muharram set by Caliph Umar Bin Khattab. The determination and calculation of days, months and years in the hijri calendar has an important role in Islam along with the problems of life and law in Islam which require the number of days in the hijri calendar. The events of the Prophet SAW when he lived in Makkah and then moved to Medina also accompanied the verses of the Qur'an that were handed down to the Prophet SAW. The migration of the Prophet SAW to Medina shows the golden age and glory of Islam.